A Restorative Justice Approach To Resolving Children's Cases With The Law - Aldi Nuryasva; Fikrotul Jadidah (IHSA Institute, 2022)
The concept of Restorative Justice as an alternative settlement of juvenile criminal cases. Restorative justice is defined as a process in which all parties related to certain crimes sit together to solve problems and think about how to deal with victims and legal actors, continue to prioritize the principle of the best interests of children and the sentencing process is a last resort while not ignoring children's rights. If the legal process continues to the reporting process to the Police, then basically the implementation of the law is through diversion efforts carried out by the police using discretionary authority.